2009
DOI: 10.1038/onc.2009.116
|View full text |Cite
|
Sign up to set email alerts
|

Ror2, a developmentally regulated kinase, promotes tumor growth potential in renal cell carcinoma

Abstract: Inappropriate kinase expression and subsequent promiscuous activity defines the transformation of many solid tumors including renal cell carcinoma (RCC). Thus, the expression of novel tumor-associated kinases has the potential to dramatically shape tumor cell behavior. Further, identifying tumor-associated kinases can lend insight into patterns of tumor growth and characteristics. Here, we report the identification of Ror2, a new tumor-associated kinase in RCC cell lines and primary tumors. Ror2 is an orphan r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
126
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(139 citation statements)
references
References 28 publications
9
126
0
Order By: Relevance
“…We previously reported that Ror2 expression has a distinct role in RCC tumor cell biology (7) and has the potential to be important for components of tumor invasion. We have since demonstrated a mechanism of Ror2 regulation that, with respect to clear cell RCC, can be linked to VHL loss and is a component of the HIF-dependent transcriptional program in clear cell RCC cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that Ror2 expression has a distinct role in RCC tumor cell biology (7) and has the potential to be important for components of tumor invasion. We have since demonstrated a mechanism of Ror2 regulation that, with respect to clear cell RCC, can be linked to VHL loss and is a component of the HIF-dependent transcriptional program in clear cell RCC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…We have identified Ror2 expression as a characteristic of many renal cell carcinoma (RCC) 2 cell lines and human tumors (7), where its expression is associated with increased cell migration and anchorage-independent growth. Ror2 also plays a prominent role in osteosarcoma (8) and has recently been identified in squamous cell carcinoma of the head and neck, where expression parallels the development of invasive features of these tumors (9).…”
mentioning
confidence: 99%
“…Recent publications have further implicated Wnt5a-Ror2 in various processes of mammalian cell migration including mediation of chemotactic responses, convergent extension, and cell invasiveness in the palate, gut, and osteosarcoma lines, respectively (He et al, 2008;Enomoto et al, 2009;Yamada et al, 2010). Ror2 as a biomarker and therapeutic target for metastatic cancers is also an active area of research (Morioka et al, 2009;Wright et al, 2009;Debebe and Rathmell, 2015).…”
Section: Wnt5a-ror2 In Cell Migrationmentioning
confidence: 99%
“…Ror2 is found heavily phosphorylated in the kidney of RCC patients and is expressed highly in human RCC cell lines indicating a role for Ror2 in the pathology of RCC (Wright et al, 2009). In fact suppressed expression of Ror2 results in reduced expression of matrix metalloproteinase (MMP)-2, whose upregulation correlates with advanced stages of RCCs (Slaton et al, 2001).…”
Section: Hif Targets-ror2mentioning
confidence: 99%